ACROM. Una herramienta para el análisis de curvas de luz cromáticas de CoRoT - Dorado Daza, Derian Jesus (Scientia et Technica, 2018)
This work presents a first version of Acrom; a set of scripts written in python language for the analysis of exoplanet light curves registered in different colors by the CoRoT satellite. It contains functionalities for filtering, detrending, phase diagram and plotting.This work proposes a particular case of convolution to deal with the long-term trend of light curves; framed in general procedure described step by step.This tool has been tested in the analysis of this light curves with the purpose of exploring the achromatic nature of the planets discovered in this survey. The results obtained during the analysis of the chromatic light curves of some CoRoT exoplanets are presented in the respective section. These results allowed to verify the achromatic behavior of the planetary transits.